2019
DOI: 10.1515/jcim-2018-0218
|View full text |Cite
|
Sign up to set email alerts
|

Role of antioxidant supplementation in oxidant/antioxidant status and hepatotoxic effects due to aflatoxin B1 in wheat miller workers

Abstract: Background Aflatoxin B1 (AFB1) is classified as a Group I carcinogen. A Previous study found that oxidative stress from the metabolism of AFB1 induced hepatotoxic effects in wheat miller workers. Zinc and vitamin C may play a significant role in the activation of detoxification and overcoming the oxidative stress of AFB1. Objectives A prospective clinical trial was designed to evaluate the role of zinc and vitamin C oral supplementation on the oxidant-antioxidant status and the hepatotoxic effects of AFB1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…Animals exposed to AFB1 have a decrease in the amount of antioxidant enzymes and an increase in markers of oxidative stress [ 17 , 20 ]. Thus, treatment with antioxidant agents may provide protection against oxidative stress and, consequently, reduce the carcinogenic potential of these substances [ 37 , 38 ]. Finally, the importance of epigenetic lesions, mainly DNA methylation and modifications in histones, cannot be discarded in genotoxicity and mutagenicity processes [ 39 ].…”
Section: Effects Of Prenatal Exposure To Aflatoxin B1 In Animalsmentioning
confidence: 99%
“…Animals exposed to AFB1 have a decrease in the amount of antioxidant enzymes and an increase in markers of oxidative stress [ 17 , 20 ]. Thus, treatment with antioxidant agents may provide protection against oxidative stress and, consequently, reduce the carcinogenic potential of these substances [ 37 , 38 ]. Finally, the importance of epigenetic lesions, mainly DNA methylation and modifications in histones, cannot be discarded in genotoxicity and mutagenicity processes [ 39 ].…”
Section: Effects Of Prenatal Exposure To Aflatoxin B1 In Animalsmentioning
confidence: 99%
“…This can result in oxidative stress owing to an imbalance between limited antioxidant defenses and the excessive formation of ROS, resulting in the damage of biological molecules including lipids, proteins, and DNA in cellular systems [34,35]. In support of this hypothesis, several studies have demonstrated the potential for antioxidants to lower the risk of hepatotoxicity caused by exposure to the AF [29,[36][37][38][39]. Moreover, many studies have reported the pivotal role of oxidative stress induced by AF in eliciting programmed cell death or apoptosis through mitochondrial signaling pathways [25,[40][41][42].…”
Section: Discussionmentioning
confidence: 97%
“…A likely explanation of this association is not yet identified, though consumption of AF-contaminated foods and feeds were reported to cause diverse degrees of liver injury comprising development of fatty cysts, fibrosis, and cirrhosis among humans and animals [23][24][25][26][27]. However, several lines of evidence support oxidative stress as a key factor in AF induced initiation and progression of liver cirrhosis [28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blood sample analysis of the worker revealed a doubling of vitamin C and Zn concentration and reduction of serum marker enzymes, i.e., aspartate aminotransferase (AST), alkaline phosphatase (ALP), and GST in most of the individuals. 123 The effect was suggested due to the antioxidant effect of supplementation against AFB1. Vitamin E also exerted protective effects against AFB1-induced nephrotoxicity in rats.…”
Section: Cellular Effectsmentioning
confidence: 99%